2017
DOI: 10.1080/17453674.2017.1399643
|View full text |Cite
|
Sign up to set email alerts
|

Fast-tracking for total knee replacement reduces use of institutional care without compromising quality

Abstract: Background and purposeFast-tracking shortens the length of the primary treatment period (length of stay, LOS) after total knee replacement (TKR). We evaluated the influence of the fast-track concept on the length of uninterrupted institutional care (LUIC) and other outcomes after TKR.Patients and methods4,256 TKRs performed in 4 hospitals between 2009–2010 and 2012–2013 were identified from the Finnish Hospital Discharge Register and the Finnish Arthroplasty Register. Hospitals were classified as fast track (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…The median LOS was 3 days, which is similar to what has been reported in the recent literature [1,3,5,6,10]. A few studies report a median LOS of 2 days [7,15].…”
Section: Length Of Staysupporting
confidence: 86%
“…The median LOS was 3 days, which is similar to what has been reported in the recent literature [1,3,5,6,10]. A few studies report a median LOS of 2 days [7,15].…”
Section: Length Of Staysupporting
confidence: 86%
“…2015, Pamilo et al. 2018) included patients operated with TKA during the same time period as the patients in our study, but in fast-track hospitals. These studies showed an incidence of MUA of almost 6%, which was comparable to the hospital in Sweden with the highest incidence (5%).…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study reported on the incidence of MUA in 1 hospital during the first 6 months after the primary knee arthroplasty surgery, before and after implementing fast-track (Pamilo et al. 2018). They found a similar incidence before (2009–2010) and after (2012–2013) fast-track (6%).…”
mentioning
confidence: 99%
“…The surgical incision, as a mechanical factor, affects the nociceptor, initiates the pain process, and triggers numerous inflammatory mediators [1,4,5]. The Enhanced Recovery After Surgery (ERAS) with the method multimodal analgesia accelerates the patient's returning to full activity [4][5][6][7][8][9][10] and limits the complications and time of hospitalization [9][10][11][12][13][14]. Of interest is whether ERAS protocol is effective in the group patients older than 65 years, who more commonly suffer from concomitants diseases and whose comorbidities are more advanced; the physiological functional reserve is decidedly lower due to systemic involution [10][11][12][13]15].…”
Section: Introductionmentioning
confidence: 99%